THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND SELF-EFFICACY ON THE PERFORMANCE OF IAIN CURUP LECTURERS - Jumira Warlizasusi; Ifnaldi Ifnaldi (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
The objective of this study is to determine whether there is a direct or indirect effect of transformational leadership and self-efficacy on the performance of IAIN Curup lecturers. Based on pre-observation, the low frequency of lecturers' attendance which did not reach sixteen meetings, the difficulty to meet the Academic advisor for consultation, inappropriate expertise of lecturers, and some of the incompetent lecturers became the background leading the researchers to examine the performance of the IAIN Curup lecturers. In this study, there were three variables. A purposive sampling was used to involve all official lecturers as the participants, and they were 112 people. This study used a quantitative approach as the research methodology by applying a survey method with path analysis technique. This study used questionnaire as the data collection technique. The researchers had analyzed the instrument before it was distributed to the participants. The instrument was tested by using validity and reliability tests. Three hypotheses were tested. The results showed that transformational leadership had a direct, positive effect on job performance; self-efficacy had a direct, positive effect on the lecturers’ job performance; and the transformational leadership had a direct effect on self-efficacy.